THE GEOGRAPHY OF 1990S INTERNET GOVERNANCE - Grosse, Meghan (AoIR Selected Papers of Internet Research, 2023)
In April 2014, after Edward Snowden revealed a widespread, global spying program carried out by the U.S. government against citizens and world leaders, Brazil hosted a meeting of NETmundial, the Global Multistakeholder Meeting on the Future of Internet Governance, to discuss moving away from a U.S.-centric oversight of internet governance structures and towards a global multistakeholder model. In 2016, the contract between the Internet Corporation for Assigned Names and Numbers (ICANN) and the U.S. Department of Commerce expired, nearly 20 years after it was first established. While the end of that contract did meaningfully address some of the concerns raised by NETmundial, there are many ways in which the U.S.’s powerful position in developing the early commercial internet is still visible. This research seeks to address the question: In what ways were early decisions about the governance of the commercial web shaped by cultural imperialist logics and how was that reflected in policy developed in the mid to late 1990s? I address this question using archival analysis focusing on the Ira Magaziner Electronic Commerce papers at the Clinton Presidential Library in Little Rock, Arkansas, arguing that the U.S. incorporated little to no input from many countries, a move that stood in contradiction with narratives coming from that administration that highlighted the internet’s potential for open, equitable, global participation.